Alternate‐stacked Li4Ti5O12 nanosheets/d‐Ti3C2 flexible film as a current collector‐free, high‐capacity and robust cathode for rechargeable Mg batteries. Issue 1 (28th June 2020) - Yang, Chaoran; Yang, Lanlan; Chai, Zhigang; Zheng, Xiang; Li, Jianming; Yang, Yuying; Zhu, Jiefang; Jin, Xu; Li, Qi; Xu, Dongsheng
Abstract: Rechargeable magnesium batteries (RMBs) have gained increasing attention owing to its high volumetric capacity, crust abundance, and safety from dendrite‐free characteristic. However, the lack of development of high‐performance cathode materials with long cycling stability and satisfactory capacity has greatly restricted the development of RMBs. Herein, a self‐supported, current collector‐free and soft electrode is prepared with delaminated Ti3 C2 (d‐Ti3 C2 ) and Li4 Ti5 O12 nanosheets by simple vacuum filtration as flexible cathode in RMBs. Fabricated into a full cell with hybrid AlCl3 /MgCl2 /Mg(TFSI)2 electrolyte and Mg anode (a thin Mg foil with thickness of 50 μm), the flexible cathode shows high initial specific capacity of 320 mAh g −1 at 20 mA g −1, excellent cycling stability (good retention even after 1000 cycles) and outstanding rate performance. Detailed mechanistic studies reveal that introduction of d‐Ti3 C2 provide fast transport paths for electrons and Mg 2+ . The enlarged layer spacing of composited d‐Ti3 C2 accounts for significant increment in capacity. Benefiting from above‐mentioned advantages, the best performance among Ti‐based electrode materials is realized and make wearable devices powered by RMBs possible, thus circumventing the safety issues of lithium batteries. Abstract : The collector‐free and self‐supporting film composed by alternate‐stacked Li4 Ti5 O12 nanosheets/d‐Ti3 C2 presents a unique three‐dimensional conductive network in which the Li4 Ti5 O12 nanosheets are evenly distributed. It exhibits excellent flexibility, electrochemical performance, and ultra‐long cycle stability. In addition, the alternate stacking of nanosheets can enlarge the interlayer spacing of d‐Ti3 C2 and stimulate its magnesium storage activity.